Hyperthermic intraperitoneal chemotherapy does not increase risk of major complication or failure to rescue in cytoreductive surgery. Issue 4 (6th June 2022) - Macfie, Rebekah C.; Cha, Da Eun; Gleeson, Elizabeth; Yu, Allen; Cohen, Noah; Sarpel, Umut; Golas, Benjamin; Hiotis, Spiros; Labow, Daniel
Abstract: Introduction: Failure to rescue (FTR) is defined as death after a major complication. We evaluated FTR after cytoreductive surgery (CRS) with and without hyperthermic intraperitoneal chemotherapy (HIPEC). Methods: The ACS NSQIP database 2005–2018 was reviewed for all cases of CRS. Propensity score matching was used to compare outcomes between those undergoing CRS alone and those undergoing CRS/HIPEC. Patients were matched on age, sex, ascites, diabetes, hypertension and resection of liver, pancreas, colon/rectum, diaphragm, stomach, small bowel, and/or spleen. Results: Thirty nine thousand one hundred and twenty‐six patients underwent CRS; 38, 387 underwent CRS alone; 739 underwent CRS/HIPEC. After matching there were 726 patients in each arm. Patients undergoing CRS/HIPEC had higher risk of reintubation (25 [3.4%] vs. 13 [1.8%] p  = 0.049), urinary tract infection UTI (44 [6.1%] vs. 25 [3.4%] p  = 0.019) and sepsis (73 [10.1%] vs. 44 [6.1%] p  = 0.005). Patients in the CRS arm required more transfusions (229 [31.5%] vs. 176 [24.2%] p  = 0.002). There was no significant difference in FTR between the CRS and CRS/HIPEC groups (11 [4.0%] vs. 6 [2.3%] p  = 0.258), nor in the pooled incidence of major complications (275 [37.9%] vs. 262 [36.1%] p  = 0.48). Conclusion: CRS/HIPEC is associated with increased rates of reintubation, UTI, and sepsis while CRS alone was associated with increased transfusion. However, the addition HIPEC to CRS did not increase the risk of pooled major complication or FTR.